Analisis Kinerja Keuangan Pada Perusahaan Asuransi Yang Terdaftar Di Bursa Efek Indonesia - Kopong, Silvester; Balun, Bernardus Somi (Tractare: Jurnal Ekonomi-Manajemen, 2023)
This study aims to determine the financial performance of insurance companies listed on the Indonesia Stock Exchange from 2016-2020 using theratio Early Warning System. The research used purposive sampling technique and the data analysis used was descriptive analysis. The ratio used in this research are fund adequancy ratio, consist of the ratio of the level of adequacy of funds, incurred loss ratio, liabilities to liquid Asset, retention ratio. The results of the analysis in this study indicate that the financial performance of insurance companies listed on the ratio of the level of adequacy of funds, incurred loss ratio, liabilities to liquid Asset is categorized as good, while judging from the retention ratio itself is in a bad condition because 3 companies experience value lower than the value set by NAIC (National Association of Insurance Commissioners).